Male view about the assistence care in the Family Health Strategy - Rosineide Santana de Brito; Danyelle Leonette Araújo dos Santos; Patrícia Suerda de Oliveira Maciel (Rev Rene)
This is a qualitative study aimed to determine the opinion of men about the assistance care received at the Family Health Strategy. Data were collected during June and July 2009 through semi structured interviews with eleven men assigned to the coverage area of a team from the Family Health Program in the municipality of Parnamirim-RN, Brazil. The statements were dealt with following the content analysis according to Bardin. The results showed to be heterogeneous as to the offered services by this Strategy, with a predominance of negative judgments due to the difficulties in getting medical care and delay in exams, besides the shortage of professionals and specialist medicine in primary services care. There was the need for a restructuring in the Basic Health Units as well as the professionals’ actions, in order to meet the healthcare demands of the male population.